Research competences and learning styles in engineering students - FARFÁN CÓRDOVA, Marlon (2019)
The research determined the relationship between research competencies and learning styles in final-year students of civil engineering of a university, and applied two instruments, the Felder and Soloman learning styles test and the research competencies questionnaire. The population was 146 students, men and women, of the curricular experiences Research Project and Development of the Research Project; with a sample of 25 women and 81 men. It turned out that the level of research skills is high for 58.5% of respondents and the predominant learning styles were moderate active, reflective discreet, sensitive moderate, intuitive discreet, visual very strong, verbal discreet, sequential moderate and global discreet. The Spearman Rho bivariate correlation analysis as a hypothesis test allowed us to conclude that the research competencies are only significantly related to active and reflective learning styles. Keywords: learning styles, skills, research.